Beta 1, Beta 2 and Beta 3 Adrenergic Receptor Gene Polymorphisms in a Southeastern European Population - Katsarou, Martha-Spyridoula; Karathanasopoulou, Aikaterini; Andrianopoulou, Angeliki; Desiniotis, Vasileios; Tzinis, Efthymios; Dimitrakis, Efthimios; Lagiou, Maria; Charmandari, Evangelia; Aschner, Michael; Tsatsakis, Aristeidis M.; Chrousos, George P.; Drakoulis, Nikolaos (Frontiers in Genetics, 2018)
Genetic polymorphisms in β1-, β2- and β3-adrenergic receptors (β-ARs) have been associated with chronic non-communicable disorders, such as cardiovascular diseases, asthma, chronic obstructive pulmonary disease (COPD) and obesity, as well as β-agonists and antagonists response and toxicity. The purpose of this study was to determine the frequency distribution of ADRB1 genetic variants Ser49Gly and Arg389Gly, ADRB2 variants Gly16Arg and Gln27Glu, ADRB3 variant Trp64Arg in a Southeastern European Caucasian (SEC) population sample and to establish a comparison with existing data from other human populations. A sample of 431 men and 590 women volunteered to participate in this genotyping analysis after anonymization and de-identification. Real Time PCR (Melting Curve Analysis) followed DNA extraction from buccal swabs and statistical analysis of the results was performed. The allele frequencies in the SEC population were Ser49 (90.3%), Arg389 (69.49%), Gly16 (61.61%), Gln27 (65.72%) and Trp64 (94.52%), while a Hardy-Weinberg Equilibrium (HWE) was detected in the population studied. Comparisons for the Ser49Gly, Gln27Glu and Trp64Arg allele distributions demonstrated significant differences between SEC and the European group. European subgroups comparisons showed that allele distributions were similar for 4 of the 5 SNPs between SEC and Southwestern European Caucasians (SWC), while they were quite distinct from the Northwestern European Caucasians (NWC). These data underline the importance of interethnic variability of β-ARs genetic polymorphisms.